A New Approach for Testing Fetal Heart Rate Monitors - Bibbo, Daniele; Klinkovsky, Tomas; Penhaker, Marek; Kudrna, Petr; Peter, Lukas; Augustynek, Martin; Kašík, Vladimír; Kubicek, Jan; Selamat, Ali; Cerny, Martin; Bielcik, Daniel (Sensors (Basel, Switzerland), 2020)
In this paper, a new approach for the periodical testing and the functionality evaluation of a fetal heart rate monitor device based on ultrasound principle is proposed. The design and realization of the device are presented, together with the description of its features and functioning tests. In the designed device, a relay element, driven by an electric signal that allows switching at two specific frequencies, is used to simulate the fetus and the mother's heartbeat. The simulator was designed to be compliant with the standard requirements for accurate assessment and measurement of medical devices. The accuracy of the simulated signals was evaluated, and it resulted to be stable and reliable. The generated frequencies show an error of about 0.5% with respect to the nominal one while the accuracy of the test equipment was within ±3% of the test signal set frequency. This value complies with the technical standard for the accuracy of fetal heart rate monitor devices. Moreover, the performed tests and measurements show the correct functionality of the developed simulator. The proposed equipment and testing respect the technical requirements for medical devices. The features of the proposed device make it simple and quick in testing a fetal heart rate monitor, thus providing an efficient way to evaluate and test the correlation capabilities of commercial apparatuses.
Keywords: fetal heart rate; Ultrasonography; tests of medical device; Heart Rate; Pregnancy; těhotenství; Fetus; srdeční frekvence; doppler effect; heart movement simulator; monitorování fyziologických funkcí; plod; srdeční frekvence plodu; lidé; fetal heart rate monitor device; Monitoring, Physiologic; ženské pohlaví; Humans; Heart Rate, Fetal; cardiotocograph; Female; ultrasonografie